Steam Locomotive Depot on a Siding – Urban Potential of Railway Wasteland - BALCER-ZGRAJA, Małgorzata (Architecture, Civil Engineering, Environment, 2025)
Within a project: “A Vision of Multifunctional Mobility and Service Structure on the Basis of the Facilities of the Former Steam Locomotive Depot in the City of Katowice”, a variant study was performed to investigate the possibilities of adaptation of a neglected, technical monument in Silesia to the needs of a city centre. It was conducted by the Faculty of Architecture, at the Silesian University of Technology in 2024. The investigations searched for methods of an effective “invisible stitching” of the urban tissue gashed with rail tracks [ ] based on old railway buildings. It was revealed that the depot area had great potential in the process of revitalizing public space. In the context of the progressive destruction of the monument, the words of Heinrich Heine (1843): [ ] take on new meaning. Methods: literature and desk research, in-situ investigations and design research. The point of departure for this study was: preparation of the site inventory as well as results of the survey presented by the Association “Congress for the Protection of Monuments” – the partner of the project.